The Idea of Gebrauchsmusik – Revisited: Paper from the conference: Neue Sachlichkeit, Political Music, or Vernacular Avant-Garde? Hanns Eisler and his Contemporaries - Hinton, Stephen (Danish Yearbook of Musicology, 2019)
The author revisits the history of Gebrauchsmusik, a musicological term that was coined in the early 1920s in musicological circles and which soon became a slogan with international currency. In documenting shifts in the term’s meaning and cultural significance and scrutinizing the role it has played in musicological discourse, the author reviews his own scholarly biography, from 1970s England, via Berlin during the 1980s, to his current home in the US. Apart from Paul Hindemith, who is widely but wrongly credited with having invented the word, composers discussed here who were similarly working in a culture that promoted the idea of Gebrauchsmusik include Hanns Eisler and Kurt Weill.